2022
DOI: 10.1088/1741-2552/ac9e1e
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Schwann cells overexpressing POU6F1 promote sciatic nerve regeneration within acellular nerve allografts

Abstract: Objective. Acellular nerve allograft (ANA) is an effective surgical approach used to bridge the sciatic nerve gap. The molecular regulators of post-surgical recovery are not well-known. Here, we explored the effect of transgenic Schwann cells (SCs) overexpressing POU domain class 6, transcription factor 1 (POU6F1) on sciatic nerve regeneration within acellular nerve allografts. we explored the functions of POU6F1 in nerve regeneration by using a cell model of H2O2-induced SCs injury and transplanting SCs overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The analysis revealed that 10 hub genes were enriched in POU6F1, which is a member of the POU factor family of transcription factors. 46 Interestingly, in the present study, POU6F1 was identified to have a low expression in tumor tissues, when compared to normal tissues. Another study reported that downregulation of POU6F1 in lung adenocarcinoma (LUAD) is associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 39%
“…The analysis revealed that 10 hub genes were enriched in POU6F1, which is a member of the POU factor family of transcription factors. 46 Interestingly, in the present study, POU6F1 was identified to have a low expression in tumor tissues, when compared to normal tissues. Another study reported that downregulation of POU6F1 in lung adenocarcinoma (LUAD) is associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 39%
“…The preserved ECM components create a milieu similar to peripheral nerve tissue for schwann cell adhesion and proliferation ( Su et al, 2022 ). Some studies show that removing the factors inhibiting axonal growth from ECM will enhance the effect of acellular nerve allograft (ANA) ( Li et al, 2022 ). Our team developed a ANA product approved by the Chinese Food and Drug Administration (CFDA) (Guangzhou Zhongda Medical Devices Company, Guangzhou, Guangdong Province, China; Approval No.…”
Section: Discussionmentioning
confidence: 99%